(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Granular Pile is one of the innovative technique, which is increase the load carrying capacity and decrease the swellshrinkage properties of expansive soils. The installation of granular pile has been proved successful in improving soft marine clays, which are very poor strength and compressibility criteria. The technique of granular pile has applied in expansive soil too, to reduce its swelling behavior. Granular piles are the most natural and ecologically neutral foundation system in existence. Granular piles consist natural material like river sand, gravel, stone or stone chips with sand etc